Rehabilitating agriculture and promoting food security following the 2010 Pakistan floods: Insights from South Asian experience - Dorosh, Paul A.; Malik, Sohail; Krausova, Marika (International Food Policy Research Institute, 2010)
The recent floods in Pakistan have had a devastating effect on the Pakistani population. The Office for the Coordination of Humanitarian Affairs (OCHA 2010) estimates that, as of early September 2010, more than 20 million people had been displaced by the flood and by some estimates the damage to crops, housing, other buildings, roads, and irrigation infrastructure now reaches $6.5 billion (OCHA 2010).* Recovery experiences from previous natural disasters in Pakistan and throughout South Asia, especially the 2005 earthquake in Pakistan and the 1998 flood in Bangladesh, suggest lessons in four broad areas that are relevant for recovery efforts following the 2010 Pakistan flood. First, market and trade policies should be clear, transparent, and consistent, maintaining adequate price incentives so that private trade and imports can contribute to postdisaster recovery. Restoration of private trade (and even promotion of expansion of trade) can enhance both price stability and food security more effectively and at far less cost than otherwise, particularly in the rehabilitation phase. Recovery experiences from previous natural disasters in Pakistan and throughout South Asia, especially the 2005 earthquake in Pakistan and the 1998 flood in Bangladesh, suggest lessons in four broad areas that are relevant for recovery efforts following the 2010 Pakistan flood. Second, there is a need for a strong institutional framework to coordinate the large-scale disaster response. Long-term and short-term goals need to be accounted for and integrated into a comprehensive postdisaster response framework. Involvement of all affected stakeholders in the policy formulation is important to ensure representation and participation. Third, recovery efforts should also include support for livelihood security and restoration and ensure inclusion of the stakeholders. In the immediate aftermath of the floods, a provision of compensation based on loss of livelihoods might be necessary to assist affected groups. Alternative strategies for the poor to cope with the loss of income need to be examined (including credit provision) so as to avoid high and unsustainable household indebtedness. Fourth, evaluation of previously implemented projects suggests that focus on not only restoring infrastructure facilities but also upgrading them can lead to enhanced flood resistance as well as a reduction in future disaster loss. In addition, the resumption of normal agricultural activities as soon as possible is vital for the country's recovery. The provision of inputs to affected smallholders is necessary for the resumption of normal livelihood activities. The 2010 Pakistan National Disaster Response Plan incorporates some of these lessons learned from earlier disasters. However, despite the establishment of national and sub-national disaster management authorities, significant challenges to the functioning of this system still remain. Two alternative institutions present themselves as possible vehicles for the delivery of poverty-alleviating interventions and resources-the Pakistan Poverty Alleviation Fund (PPAF) and the Benazir Income Support Programme (BISP). PPAF uses a participatory and community-based model and comprises a network of more than 130,000 community organizations and groups in 127 districts covering 30,000 villages. This large and established network puts PPAF in a convenient position to reach affected communities in a timely and efficient manner. BISP has a partnership with the National Database and Registration Authority (NADRA) that is being used to provide necessary financial support to flood victims throughout the country. However, there are several obstacles to the successful disbursement of funds through BISP. In particular, because a large percentage of displaced people do not possess computerized national identity cards, these people could be excluded from the income support programs unless a new comprehensive listing is done. Finally, it is important to establish and strengthen disaster response capability so that the country can better respond to recurring natural disasters. Emergency early warning system mechanisms have the potential to substantially reduce casualties and economic losses from disasters, and they need to be strengthened. Likewise, the lessons learned from the relief and rehabilitation response to the 2010 floods should be incorporated in contingency plans for future natural disasters.